Efficiency and safety of various dual antiplatelet therapy strategies in patients undergoing percutaneous coronary intervention due to myocardial infarction - S. B. Aksentiev; A. V. Solovieva; D. S. Yunevich (Российский кардиологический журнал)
Aim. To compare the efficacy and safety of prasugrel, ticagrelor, or clopidogrel as part of dual antiplatelet therapy (DAPT) in patients undergoing percutaneous coronary intervention (PCI) due to myocardial infarction (MI).Material and methods. The observational study included 74 patients who underwent PCI due to MI within the first 24 hours after the onset. The patients were devided into 3 groups: group 1 — patients who received ticagrelor as part of DAPT; group 2 — clopidogrel, group 3 — prasugrel. The follow-up period was 28 days. To assess the efficacy and safety of therapy, a composite endpoint was assessed (death + nonfatal recurrent MI (and/or stent rethrombosis) + nonfatal ischemic stroke (IS). Additional secondary endpoints were any moderate and severe (major) bleeding according to the GUSTO and/or TIMI scales. We assessed the incidence of reperfusion arrhythmias, an opening of an infarct-related coronary artery (IRCA), and non-ST elevation myocardial infarction (non-STEMI).Results. The analysis showed no significant differences in the cumulative incidence of adverse outcomes in the study groups within 28 days. The prevalence of secondary endpoints over a 28-day follow-up period was 3,1% in the ticagrelor group and 5,9% in the clopidogrel group, while no moderate and life-threatening bleeding was recorded in the prasugrel group during. There were no significant differences in the incidence of reperfusion arrhythmias, opening of an IRCA, and non-STEMI between the groups.Conclusion. The obtained results suggest the comparable efficacy and safety profiles of prasugrel, ticagrelor and clopidogrel as a part of DAPT in patients undergoing PCI due to MI. There were no significant differences in endpoint event rates. In particular, prasugrel has been shown to be as effective and safe as ticagrelor.